Mental Pain and Suicide: A Systematic Review of the Literature - Verrocchio, Maria Cristina; Carrozzino, Danilo; Marchetti, Daniela; Andreasson, Kate; Fulcheri, Mario; Bech, Per (Frontiers in Psychiatry, 2016)
Background: Mental pain, defined as a subjective experience characterized by perception of strong negative feelings and changes in the self and its function, is no less real than other types of grief. Mental pain has been considered to be a distinct entity from depression. We have performed a systematic review analyzing the relationship between mental pain and suicide by providing a qualitative data synthesis of the studies. Methods: We have conducted, in accordance with PRISMA guidelines, a systematic search for literature in PubMed, Web Of Science, and Scopus. Search terms were ‘mental pain’ “OR” ‘psychological pain’ OR ‘psychache’ combined with the Boolean “AND” operator with ‘suicid*’. In addition, a manual search of the literature, only including the term ‘psychache’, was performed on Google Scholar for further studies not yet identified. Results: Initial search identified 1450 citations. A total of 42 research reports met the predefined inclusion criteria and were analyzed. Mental pain was found to be a significant predictive factor of suicide risk, even in the absence of a diagnosed mental disorder. Specifically, mental pain is a stronger factor of vulnerability of suicidal ideation than depression. Conclusions: Mental pain is a core clinical factor for understanding suicide, both in the context of mood disorders and independently from depression. Health care professionals need to be aware of the higher suicidal risk in patients reporting mental pain. In this regard, psychological assessment should include a clinimetric evaluation of mental pain in order to further detect its contribution to suicidal tendency.